NOVEL ‘‘TURN-ON’’ FLUORESCENT CHEMOSENSOR FOR THE SELECTIVE DETECTION OF HG2+ AND THEIR LIVE CELL IMAGING - Sivalingam Lakshmanan (International Journal of Modern Agriculture, 2020)
We have designed, synthesized, and evaluated a novel 2-hydroxynaphthalene-1,4-dione derivative based ‘‘turn on’’ fluorescent chemosensor (L1, L2)for the detection of Hg2+ ions in THF:H2O.The fluorescent spectra changes observed upon addition of various metal ions show that L1, L2 is highly selective for Hg2+ over other metal ions. An important feature for the new chemosensor probe displayed an apparent colour change, which could be observed by under a UV lamp. Experimental results have been verified with DFT and TDDFT calculation. Confocal fluorescence microscopy imaging using cells showed that (L1, L2) could be used as an effective fluorescent probe for detecting Hg2+in living cells